Contemporary pedagogic currents and teaching styles in the physical education - Borda Hurtado, Jaime (2014)
The study is about the principals Contemporary Pedagogic Currents that have marked and mark the formation of the man. It has been considered the components of each one of them, analyzing them and comparing them with styles or teaching methods of the Physical Education, proposed by Muska Mosston; was taken as basic aspects the educational conception, the purposes of the education, the relationships between teacher-student, the educational contents, the methodology and the evaluation. There was executed a investigation descriptive – comparative, which had as intention determine the existing relation between teaching styles of the Physical Education and the pedagogic currents, reaching at the conclusion that the teaching styles have a direct relation with the educational conception of pedagogic currents.